Tantangan dan Peluang AI dalam Mewujudkan Keadilan Hukum di Era Teknologi - Achmad Hariri (‎Fakultas Hukum Universitas Jember, 2025)
The development of information technology, particularly Artificial Intelligence (AI), has brought significant changes across various sectors, including the legal enforcement system. AI offers efficiency, speed, and accuracy in processing legal data, jurisprudential analysis, and supporting decision-making processes. However, behind these opportunities lie several challenges, such as concerns over algorithmic bias, personal data protection, and the potential dehumanization of legal procedures. This article critically examines the role of AI in supporting legal justice, identifies its potential and the obstacles faced in its implementation, and provides recommendations for the ethical and transparent application of AI that upholds the principles of justice. Using a normative approach and literature review, this paper aims to provide an initial overview of how technology can collaborate with the legal system to realize inclusive justice that is adaptive to the times.